2006
DOI: 10.1007/s10620-006-8014-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Ischemia-Reperfusion Injury: Roles of Ca2+ and Other Intracellular Mediators of Impaired Bile Flow and Hepatocyte Damage

Abstract: Liver resection and liver transplantation have been successful in the treatment of liver tumors and end-stage liver disease. This success has led to an expansion in the pool of patients potentially treatable by liver surgery and, in the case of transplantation, to a shortage of liver donors. At present, there are significant numbers of potential candidates for liver resection and liver donation who have fatty livers, are aged, or have livers damaged by chemotherapy. All of these are at high risk for ischemic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 139 publications
(173 reference statements)
1
51
0
Order By: Relevance
“…Increased cytosolic Ca 2+ is a key event in the pathological process of I/R injury because Ca 2+ can induce the opening of mitochondrial permeability transition pore and lead to mitochondrial swelling and the release of cyt c from mitochondria, initiating cell apoptosis and necrosis (31,32). A rapid increase in hepatocyte Ca 2+ was detected after the onset of reperfusion, but not during the ischemic phase (33). In the present study, we show that mitochondrial CBS accumulation during liver ischemia is associated with increased production of H 2 S in mitochondria, and H 2 S inhibits Ca 2+ -induced cyt c release and mitochondrial swelling in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cytosolic Ca 2+ is a key event in the pathological process of I/R injury because Ca 2+ can induce the opening of mitochondrial permeability transition pore and lead to mitochondrial swelling and the release of cyt c from mitochondria, initiating cell apoptosis and necrosis (31,32). A rapid increase in hepatocyte Ca 2+ was detected after the onset of reperfusion, but not during the ischemic phase (33). In the present study, we show that mitochondrial CBS accumulation during liver ischemia is associated with increased production of H 2 S in mitochondria, and H 2 S inhibits Ca 2+ -induced cyt c release and mitochondrial swelling in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 During ischemiareperfusion injury, NO has a protective effects by scavenging free radicals, relaxing vascular smooth muscle, and affecting antiapoptosis. 6,7 Inhalation of NO gas after liver transplant lowers hepatocyte apoptosis. 8 During acute rejection, vascular endothelial cell damage occurs, and the eNOS pathway may be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Microvilli in bile canaliculus epithelial cells consist of Factin microfilaments, which are very important for bile excretion [7] . The continuous assembly and disassembly of Factin microfilaments promote bile duct contraction and bile excretion; therefore, the loss of Factin microfilaments leads to bile secretion disorder [9,10] . Some researchers have confirmed that cofilin and heat shock protein 27 (HSP27) are very important in the assembly and disassembly of F-actin microfilaments [11,12] .…”
Section: Introductionmentioning
confidence: 99%